Social diversity and people’s relocation, another challenge in the Bogota River restoration process (REVISTA NODO, 2012)
The article approaches the Bogota River environmental and hydraulic restoration process from a social perspective. Taking World Bank’s considerations for financing this particular kind of endeavors, it starts by analyzing the physical and social complexities of those lots required to execute the project, finding three different types of land ownership: private property, public property and river bank improvement possession. Then, it studies the Social Management Plan projected by the CAR (Regional Autonomous Corporation, in Spanish) —with the consultancy of one of the authors as part of the World Bank—, which proposes several solutions to the various social and economic conditions of landowners and property possessors. Finally, it concludes that different attention when it comes to institutions, private proprietors and vulnerable families in possession imply countless strategies that make the Bogota River restoration management task even more complex.
Keywords: Social management plans; social methodologies; environmental reserve zones